Biosistemática del género Petrejoides Kuwert (Coleoptera, Lamellicornia, Passalidae) - Castillo, Camelia; Reyes Castillo, Pedro (Instituto de Ecología, A.C., 1984)
We studied the taxonomy of the Proculini genus Petrejoi- des Kuwert based on 600 specimens from different mexican and central american localities. We established the phyletic relationships of this genus within the tribe Proculini by defining 12 species, four of these species endemic to México are descríbed here. In the genus Petrejoides we distinguished three phyletic Unes. Orizabae line: composed by P. orizabae Kuwert, P. silváticas sp. nov. (MEXICO: Nuevo León; northern Sierra Madre Oriental, Chipinque-Cola de Caballo región), P. subrecticornis (Kuwert), P. jalapensis (Bates) and P. guatemalae Reyes-Castillo and Schuster. Laticornis Wne: oniy P. laticornis (Truqui). "Recticornis line: composed by P. recticornis (Burmeister), P. nebulosas sp. nov. MEXICO: Hidalgo: cloud forest in the vicinity of Tenango de Doria), P. olmecae sp. nov. (MEXICO: Guerrero: wet slopes of the Sierra Madre del Sur, distributed through the cloud forest in the Omiltemi región), P. imbe- 2 Castillo, C. y P. Reyes-Castillo. Blosistemática de Petrejoides llis (Casey), P. mazatecus sp. nov. (MEXICO: Oaxaca: Sierra de Zongolica of the Sierra Madre Oriental, cloud forest in the vincity of Huautia de Jiménez), and P. tenuis Kuwert. We discussed the taxonomic characters and affinities of these three phyietic línes and we inelude an Identification key of the species. Every species is described or redescribed, discussing their varíations and affinities synonyms and comments, and are depicted for a better understanding of taxonomic characters used for description. Based on taxonomic affinities, ecological requirements and geographical distribution, we concluded that Petrejoides shows the Mesoamerican Mountain dispersal pattern with projections into Southern Central America. This is a typical montane taxa, preferently hygrophilous and completely sylvicolous. It shows a great diversification in the mountains located northwesterly to the Istmo de Tehuantepec, where the three phyietic lines oceur and is rich in endemic forms. In the Central American Nucleus, assumed as the origin area of Petrejoides, there is a low number of species which is, ap- parently, relatad with the diversification of Chondrocephalus these two genera have the highest affinities and share their rangas. In the Mexican Transition Zone speciation processes and the establishment of dispersal patterns of Petrejoides are highiy influenced by the distribu- tion and evolution of the cloud forest. The invasión of the mountains located to the north-west of the Istmo de Tehuantepec, probably was an event carried out in the earlier stages of the evolution of this genus. We assumed it based on the presence in this area of plesio- morphic and apomorphic species. opposed to the invasión of Southern Central America (Costa Rica, Panama) which has been a relatively recent event.